Specifying the Academic Language Skills That Support Text Understanding in the Middle Grades: The Design and Validation of the Core Academic Language Skills Construct and Instrument. Issue 4 (18th June 2019) - Barr, Christopher D.; Uccelli, Paola; Phillips Galloway, Emily
Abstract: This study reports on the conceptualization of a new construct targeting the cross‐disciplinary academic language skills most relevant to school reading comprehension, targeting the validation of the Core Academic Language Skills (CALS) Instrument, a novel assessment tool which measures this construct. Participants included Grade 4–8 monolingual English and bilingual students designated as English learners ( N = 7, 152) from the United States. The study investigated the dimensionality of the core academic language skills construct, the reliability and validity of the CALS Instrument, and the impact of school grade on students' performance in core academic language skills. Results revealed the assessment measure to be unidimensional and to discriminate performance by grade level. This study offers insight into the value of measuring cross‐disciplinary school‐relevant language proficiency, delineates skills to be targeted through instruction to support reading comprehension, and offers a tool to identify students who will benefit most from this instruction. Abstract :